1983
DOI: 10.1063/1.332611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Si and SiO2 thermal nitridation on impurity diffusion and oxidation induced stacking fault size in Si

Abstract: The effect of thermal nitridation on impurity diffusion and Oxidation Induced Stacking Fault (OSF) size in Si are clarified by selective nitridation. Enhanced Band P diffusion, retarded Sb diffusion, and growth of OSP's are found in Si masked with Si0 2 films. Retarded Band P diffusion, enhanced Sb diffusion and rapid OSF shrinkage are found in nonmasked Si that has undergone NH3 heat treatment. On the other hand, in N2 or N2 + H2 (1:3) ambients, no significant ambient effect on impurity diffusion is found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 11 publications
4
28
0
2
Order By: Relevance
“…This points to a supersaturation of native point defects established by B diffusion. Additional results on B diffusion in Si isotope structures obtained at different temperatures, on enhanced (retarded) B diffusion under I (V) injection [129,132] and of isoconcentration diffusion experiments [133] reveal the charge states of the mobile B-related defect and of the native point defects involved in B diffusion. Altogether, B diffusion in Si under various experimental conditions is consistently described by the following reactions [64] with neutral (I 0 ), singly and doubly positively (I C , I 2C ) charged self-interstitials and neutral (V 0 ), singly positive (V C ), and singly and doubly negative (V , V 2 ) vacancies.…”
Section: Diffusion Profiles Of Dopant Atomsmentioning
confidence: 96%
See 1 more Smart Citation
“…This points to a supersaturation of native point defects established by B diffusion. Additional results on B diffusion in Si isotope structures obtained at different temperatures, on enhanced (retarded) B diffusion under I (V) injection [129,132] and of isoconcentration diffusion experiments [133] reveal the charge states of the mobile B-related defect and of the native point defects involved in B diffusion. Altogether, B diffusion in Si under various experimental conditions is consistently described by the following reactions [64] with neutral (I 0 ), singly and doubly positively (I C , I 2C ) charged self-interstitials and neutral (V 0 ), singly positive (V C ), and singly and doubly negative (V , V 2 ) vacancies.…”
Section: Diffusion Profiles Of Dopant Atomsmentioning
confidence: 96%
“…The broadening of the Si profiles demonstrates that the I supersaturation due to P diffusion is significantly lower than expected on the basis of the previous considered P diffusion models. Taking into account additional results on P diffusion in Si obtained under different experimental conditions that comprise diffusion studies under intrinsic and extrinsic doping [150,151], under defect injection [129,132,152], and under isoconcentration conditions [150], the following reactions were determined to accurately describe P diffusion in Si [64] PV P Successful modeling of the simultaneous P and Si diffusion requires a contribution of singly positively charged mobile P defects to P diffusion. Generally, the extended tail of the P profiles compared to the much steeper As profile at the diffusion front was explained with an I-supersaturation established during P diffusion.…”
Section: Diffusion Profiles Of Dopant Atomsmentioning
confidence: 99%
“…Conversely, retarded diffusion of boron was observed below nitride films with the work of Osada et al [11] as a representative example. Similar effects were observed already before by Mizuo et al [12] and others during thermal nitridation of silicon. The only problem for associating the latter with stress effects is that nitride growth stops at a thickness of a few nanometers.…”
Section: Stress and Strain Effectssupporting
confidence: 76%
“…Intrinsic phosphorus diffusion was demonstrated to be retarded under nitridation (vacancy injection) conditions [7,8]. From this retardation, it was concluded that the intrinsic P diffusion was entirely interstitially mediated [9].…”
Section: Introductionmentioning
confidence: 91%